Book Reviews / Rezensionen - Marc Lavoie; Eckhard Hein; Georg Gottholmseder; Eckhard Hein; Christa Schlager; Gisela Kubon-Gilke; Rémi Stellian; Torsten Niechoj; Hagen Krämer (Intervention. European Journal of Economics and Economic Policies, 2010)
Books reviewed: Jonathan P. Goldstein/Michael G. Hillard (eds.) (2009): Heterodox Macroeconomics: Keynes, Marx and Globalization, London Mathew Forstater/L. Randall Wray (eds.) (2008): Keynes for the Twenty-First Century. The Continuing Relevance of The General Theory, Basingstoke L. Randall Wray/Mathew Forstater (eds.) (2008): Keynes and Macroeconomics after 70 Years. Critical Assessments of The General Theory, Cheltenham Jesús Ferreiro / Serrano Felipe / Giuseppe Fontana (eds.) (2008): Fiscal Policy in the European Union, Basingstoke Giuseppe Fontana (2009): Money, Uncertainty and Time, London/New York Friederike Maier/Angela Fiedler (Hrsg.) (2008): Verfestigte Schieflagen. Ökonomische Analysen zum Geschlechterverhältnis, Berlin Jörg Schindler/Martin Held (2009): Postfossile Mobilität. Wegweiser für die Zeit nach dem Peak Oil, Bad Homburg Jesper Jespersen (2009): Macroeconomic Methodology. A Post-Keynesian Perspective, Cheltenham et al. John Grahl (ed.) (2009): Global Finance and Social Europe, Cheltenham, UK/Northampton, MA, USA Heinz D. Kurz (Hrsg.): Klassiker des ökonomischen Denkens. Band 1: Von Adam Smith bis Alfred Marshall Heinz D. Kurz (Hrsg.): Klassiker des ökonomischen Denkens. Band 2: Von Vilfredo Pareto bis Amartya Sen
Keywords: 330